Fragility Analysis of Masonry Structures Subjected to Random Sequential Ground Motions - Jialiu Pan; Lei Cao; Yongqun Zhang; Jiaxu Shen (Buildings)
In this study, a fragility analysis of masonry structures is conducted using a random sequential ground motion model. Initially, the relationship between a mainshock and its aftershocks is clarified based on the physical mechanism of “source-path-local site”. Building on this, the random sequential ground motion model is developed by integrating a point-source model with a homogeneous isotropic medium model. A five-story masonry structure model is then constructed in ABAQUS (6.14), and its accuracy is validated through experimental testing. Following this, 21 sets of random sequential ground motions are generated. Using the Incremental Dynamic Analysis (IDA) method, 1260 nonlinear response samples of the structure under varying sequential ground motions are obtained, providing an insight into the fragility of the masonry structure subjected to these ground motions.